Eficácia política de uma crítica: Paulo Emílio Salles Gomes e a constituição de uma teia interpretativa da história do cinema brasileiro - Souza, Julierme Sebastião Morais (2010)
This work aims to contribute to theoretical and methodological analysis of writing the history of Brazilian cinema. The object of this study the trilogy of articles in Cinema: the trajectory of underdevelopment regimented, the critic and historian Paulo Emílio Salles Gomes, seeks to understand the process of setting up a web interpretative history of our film based on this work and how to rescue its historicity.